Phoenix from the Flames? Promoting Entrepreneurship to support the Economic Development of Neath Port Talbot - David Pickernell (ISBE ENTREPRENEURSHIP POLICY AND PRACTICE INSIGHTS, 2024)
Executive summaryTata Steel’s 2024 decision to close the blast furnaces in Port Talbot in Wales (Pfeifer and Pickard, 2024), meaning that 2,800 of the current workforce may lose their jobs during the proposed transition to Arc-furnace-generated steel production, with huge deleterious impacts on the local and regional economy. In times of such workforce restructuring and potential layoffs, fostering a spirit of entrepreneurship can mitigate adverse impacts on individuals and contribute to the broader economic revitalisation of the region, via start-up activity. Because this process is often difficult in localities experiencing an industrial decline (Gherhes, et al., 2020), this brief delves into strategies for equipping the workforce with entrepreneurial skills and identifying potential government initiatives to support those willing to embark on entrepreneurial ventures post-layoff.